Albumin administration prevents the onset of pressure ulcers in intensive care unit patients - Serra, Raffaele (Int Wound J, 2013)
Pressure ulcers (PUs) are a common problem in critically ill patients admitted to the intensive care units (ICUs) and they account for more than 70% of patients with low serum albumin at admission. The aim of this study was to test the efficacy of intravenous administration of albumin in patients with low serum albumin < 3·3 g/dl. In a 1‐year period, a total of 73 patients were admitted to the ICU (males 45, 61·64% and females 28, 38·36%); of these, 21 patients were admitted with hypoalbuminaemia (serum albumin < 3·3 g/dl) and randomised into two groups: 11 patients were treated with 25 g intravenous albumin for the first 3 days within the first week of ICU stay (group A) and 10 patients did not receive albumin (group B). Three patients (27·27%) showed the onset of PUs in group A, whereas seven patients (70%) showed the onset of PUs within the first 7 days of stay in group B. Moreover, ulcers of group B were more severe than those of group A. This study shows that intravenous administration of albumin reduces the onset of PUs in patients admitted to the ICU and in some cases it also reduces the risk of progression to advanced stages of PUs.